Immunohistochemical evidence of local production of catecholamines in cells of the muscle origins at the lateral and medial humeral epicondyles: of importance for the development of tennis and golfer's elbow?. Issue 4 (20th January 2009) - Zeisig, E; Ljung, B-O; Alfredson, H; Danielson, P
Abstract : Background: Tennis elbow (TE) is a painful condition affecting the common extensor origin at the lateral humeral epicondyle. Colour Doppler examination has shown increased blood flow at this site and the sensory, and sympathetic innervation patterns have been delineated. However, it is not known whether there is local production of catecholamines and/or acetylcholine in this tissue, which is the case in patellar and Achilles tendinopathies. Objective: To investigate the possible presence of local production of catecholamines and acetylcholine in non-neuronal cells (fibroblasts) in connective tissue at the muscle origin at the lateral humeral epicondyle in patients with TE. Design: Immunohistochemical studies were performed on biopsies taken from the extensor origin in patients with TE and in pain-free controls. For reference purpose, biopsies from the flexor origin in patients with golfer's elbow (GE) were also studied. Patients: Seven patients with TE and four patients with GE. Six healthy asymptomatic individuals served as controls. Method: Immunohistochemistry, using antibodies detecting synthesising enzymes for catecholamines (tyrosine hydroxylase; TH) and acetylcholine (choline acetyltransferase; ChAT). Results: TH-like immunohistochemical reactions were seen in fibroblasts in four of the seven patients with TE and two of the four patients with GE. No such reactions were detected in controls (0/6). No ChAT reactions were seen in any of the investigated specimens. Conclusions: There is evidence of local, non-neuronal production of catecholamines, but not acetylcholine, in fibroblasts in the tissue at the muscle origin at the lateral and medial epicondyles in patients with TE and GE, respectively, which might have an influence on blood vessel regulation and pain mechanisms in these conditions.